The professor, "Angry Amy" - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case examines the issue of companies running criminal background checks when hiring someone. Amy Bishop shot her peers when she was denied tenure at the University of Alabama at Huntsville. Apparently, Bishop was accused of several other crimes, including killing her brother when she was 21 and a student at Northeastern University.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). The Professor, "Angry Amy." In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 101-106). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Employee screening -- Case studies; Violence in the workplace -- Case studies